Prosedur pelaksanaan konfirmasi setoran negara berdasarkan peraturan Dirjen Perbendaharaan Nomor PER-5/PB/2018 (Studi pada Kantor Pelayanan Perbendaharaan Negara Tipe A1 Malang) - Clara Rizqi Firlian; Dewi Kusumowati (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study aims to determine whether the Malang Type A1 State Treasury Service Office and the Public Service Agency have implemented the procedures for implementing state revenue deposit confirmations in accordance with the Regulation of the Director General of Treasury Number Per-5/PB/2018. This study uses a qualitative descriptive research method. Sources of data used are primary data and secondary data. The type of data in this study is the type of qualitative data. The data collection technique used is through in-depth interviews, observation, and documentation. The data is in the form of an application letter, recapitulation of state revenue deposits, ADK (Computer Data Archives), proof of state revenue deposits, then compared with the Regulation of the Director General of Treasury Number Per-5/PB/2018. The results of this study indicate that the State Treasury Service Office (KPPN) Type A1 Malang has complied with the implementation procedures in accordance with the Regulation of the Director General of Treasury Number Per-5/PB/2018 and many Public Service Agency (BLU) Satkers are not in accordance with the Regulation of the Director General of Treasury Number Per- 5/PB/2018.